From Drawing to Place.The void of the places imagined by Álvaro Siza for Malagueira - Brito, Francisco (2021)
Emptiness is as an intrinsic part of the city, as it is a path of continuous evolution or its reverse and stagnation. Because of the process, expectant spaces arise, between the opportunity and the discomfort of failed processes. Alvaro Siza’s Quinta da Malagueira estate in Évora is an example of a large urban area designed with a mixed plan that provided for housing, services, and commerce, that offer radical lessons in architecture and time. Yet, most of the public buildings - including a parish centre, a restaurant, a motel, a medical centre and the main central structure at the central public square - were left to be built and the site that would accommodate it is now an expectant urban space. The desire to complete the plan is opposed to the sense of emptiness and incompletion, which conditions its perception of its quality, as well as the desired fulfilment of genuine expansion of the city. The contradiction between the lack that these spaces make to the population and the consolidation of the urban space that remain to be realized urges discussion. These empty spaces are simultaneously a mixture of anguish and disorder that give rise to spontaneous and disorganized uses. These are nobody's spaces, not because of the absence of a cadastral owner, but because of the absence of an ordered possession. According to Ignasi de Solà-Morales definitions, these spaces are still “terrain vague”. We investigate these empty spaces or “voids” as we (re)discover what would give them the condition of “places” for which they desire. We will present these voids, the drawings that defined them, the commitments initially foreseen by Álvaro Siza in contrast with the unexpected occupations in a continuous succession of will and desire, of expectation and collapse, of (re)use and perversion. This is an anachronic record of a city enclosed in folders, drawn in ink on leaves, an imaginary of spaces that may never be lived. And of a research that fosters the idea, the project, and the materialization of Álvaro Siza’s Malagueira urban space.